Multisite left ventricular pacing in cardiac resynchronization therapy. (July 2014) - Gamble, James HP; Betts, Tim R
ABSTRACT: : Cardiac resynchronization therapy is an effective treatment for selected patients with heart failure and left bundle branch block dyssynchrony. Unfortunately, about a third of patients, so-called nonresponders, do not display any symptomatic or structural improvements after the treatment. In another 5% of patients, the left ventricular lead cannot be implanted due to technical limitations. Novel quadripolar pacing lead and associated multisite pacing technology has the potential to help improve both of these problems. The technology and applications of these leads are reviewed and the novel technique of multisite pacing from two poles of one quadripolar lead is discussed. This technology may improve response to cardiac resynchronization therapy for some patients.